Evaluasi dan Rekomendasi Strategi Kebijakan Bisnis pada PT Ananda Sukses Mandiri - Ikaningtyas, Maharani; Andarini, Sonja; Firdausi, Iasa Nur; Baharudinsyah, Mohammad Vavian; Aditya, Robby (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2023)
A business policy strategy is an important element that must be carefully formulated and studied by a company so that it does not cause multiple interpretations and is in accordance with the objectives of establishing a business or company. Reviewing this statement, the authors compiled a study using descriptive qualitative research methods with PT Ananda Sukses Mandiri as the unit of analysis within a certain period of time (cross action). The goal is that the reader can understand in more detail about the business policy strategy, and PT Ananda Sukses Mandiri can get to know the business policy strategy it has and understand what impact it will have from implementing the business policy strategy so that the company can have options whether to maintain a business policy strategy that is owned or renovate and add new business policy strategies. As for the results of his research, there are several business policy strategies that should be maintained and there are also business policies that require improvement at the implementation and formulation stages. Keywords : strategy, policy, business, evaluation, pt ananda sukses mandiri.